Repertórios sobre lesbianidade na novela Senhora do Destino: possibilidades de legitimação e de transgressão - Borges, Lenise Santana (2008)
The research on which this thesis is based sought to understand the ways of speaking about lesbianity in the soap opera Senhora do Destino (Globo Network, 2004-2005) from the perspective of discursive analysis. Television, and particularly soap operas, are a daily social practice very commom among Brazilians. The soap operas produced in Brazil are a highly popular and widely accessible source of information and entertainment. In addition, they play an important role in the production, maintenance and dissemination of selected perspectives on social questions, especially those considered taboo as in the case of lesbianity. Unlike earlier soap operas, Senhora do Destino approached the subject directly and continuously, enhancing the meanings attributed to lesbianity due to the variability of the repertories and opinions of the characters along the story. The constructionist perspective together with a feminist reading allowed me to understand the notion of lesbianity as a social construction in which the discourses and the language adopted vary according to the social and historical context. Taking this epistemological and methodological approach into account, I question the inevitability of the existence of the category lesbianity, searching for ways to look for its denaturalization, a path shared by both constructionism and feminism. The analysis was centered on discursive practices, understood as language in action and also the understanding that there are always multiple, situated and dialogical versions of conversation. For its singular characteristics, the soap opera functions as a propitious context for the definition, delimitation and resignifying of social problems . The results of this research suggest parallel effects of the introduction of the issue of lesbianity in the soap opera. On one hand, the process of assimilation of the lesbian category provokes a broader familiarity with the issue in society, as well as the presence of codes/models that allow the legitimacy of same sex relations. On the other hand, the legitimizing/acceptance processes occur in ways that do not provoke the destabilization of social norms and hegemonic models. The discursive rhetoric of the soap opera is constructed from the idea of couple , in which the primary reference is the naturalized heterosexual expression of sexuality and/or love relation, which is employed, without questioning, vis-à-vis the lesbian relationship on view